Teachers’ Multidimensional Attitude Towards Inclusive Education - Hafsa Noreen; Faiza Intizar; Sakina Gulzar (UMT Education Review, 2019)
Inclusion in education is essential for educating students with special needs. The basic pillars of inclusive education are teachers who play a key role in the social acceptance of special children and provide them social support without any distinction. It is crucial for all teachers in inclusive education to welcome special students and provide them with equal educational opportunities and environment. The current research aimed to investigate the affective, cognitive and behavioral aspects of teachers’ attitudes within the domain of inclusive education regarding physical, social and curricular inclusion using the Multidimensional Attitudes Towards Inclusive Education Scale (MATIES) developed by Mahat (2008) and their effects on special children’s learning. It was hypothesized that general education teachers who deal with mainstream students have more negative attitudes towards inclusive education as compared to special education teachers. A sample of 280 teachers was drawn from the primary and secondary inclusive schools of Punjab (Pakistan). The results were processed via SPSS-21. The study brings forward the measurement of teachers’ multidimensional attitudes towards inclusive education.